The g5R (D250) Gene of African Swine Fever Virus Encodes a Nudix Hydrolase That Preferentially Degrades Diphosphoinositol Polyphosphates - Cartwright, Jared L. (American Society for Microbiology, 2002)
The African swine fever virus (ASFV) g5R gene encodes a protein containing a Nudix hydrolase motif which in terms of sequence appears most closely related to the mammalian diadenosine tetraphosphate (Ap(4)A) hydrolases. However, purified recombinant g5R protein (g5Rp) showed a much wider range of nucleotide substrate specificity compared to eukaryotic Ap(4)A hydrolases, having highest activity with GTP, followed by adenosine 5′-pentaphosphate (p(5)A) and dGTP. Diadenosine and diguanosine nucleotides were substrates, but the enzyme showed no activity with cap analogues such as 7mGp(3)A. In common with eukaryotic diadenosine hexaphosphate (Ap(6)A) hydrolases, which prefer higher-order polyphosphates as substrates, g5Rp also hydrolyzes the diphosphoinositol polyphosphates PP-InsP(5) and [PP](2)-InsP(4). A comparison of the kinetics of substrate utilization showed that the k(cat)/K(m) ratio for PP-InsP(5) is 60-fold higher than that for GTP, which allows classification of g5R as a novel diphosphoinositol polyphosphate phosphohydrolase (DIPP). Unlike mammalian DIPP, g5Rp appeared to preferentially remove the 5-β-phosphate from both PP-InsP(5) and [PP](2)-InsP(4). ASFV infection led to a reduction in the levels of PP-InsP(5), ATP and GTP by ca. 50% at late times postinfection. The measured intracellular concentrations of these compounds were comparable to the respective K(m) values of g5Rp, suggesting that one or all of these may be substrates for g5Rp during ASFV infection. Transfection of ASFV-infected Vero cells with a plasmid encoding epitope-tagged g5Rp suggested localization of this protein in the rough endoplasmic reticulum. These results suggest a possible role for g5Rp in regulating a stage of viral morphogenesis involving diphosphoinositol polyphosphate-mediated membrane trafficking.